2011 International Joint Conference on Biometrics (IJCB) 2011
DOI: 10.1109/ijcb.2011.6117474
|View full text |Cite
|
Sign up to set email alerts
|

Robustness of multi-modal biometric verification systems under realistic spoofing attacks

Abstract: Recent works have shown that multi-modal biometric systems are not robust against spoofing attacks [12, 15,13]. However, this conclusion has been obtained under the hypothesis of a "worst case" attack, where the attacker is able to replicate perfectly the genuine biometric traits. Aim of this paper is to analyse the robustness of some multi-modal verification systems, combining fingerprint and face bio-metrics, under realistic spoofing attacks, in order to investigate the validity of the results obtained under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 13 publications
(36 reference statements)
0
15
0
Order By: Relevance
“…Similar results were obtained under the same assumption in [14], [15]. Subsequently, we carried out an extensive experimental analysis on multibiometric systems combining face and fingerprint, to evaluate whether and to what extent this assumption was representative of current techniques for fabricating fake traits (from now on, fake fabrication techniques) [17]- [19]. 3 To this end, we considered different acquisition sensors and matchers, and several presentation attacks fabricated with different techniques.…”
Section: Where We Stand Todaymentioning
confidence: 65%
See 1 more Smart Citation
“…Similar results were obtained under the same assumption in [14], [15]. Subsequently, we carried out an extensive experimental analysis on multibiometric systems combining face and fingerprint, to evaluate whether and to what extent this assumption was representative of current techniques for fabricating fake traits (from now on, fake fabrication techniques) [17]- [19]. 3 To this end, we considered different acquisition sensors and matchers, and several presentation attacks fabricated with different techniques.…”
Section: Where We Stand Todaymentioning
confidence: 65%
“…Under the same assumption, more secure fusion rules against presentation attacks have also been proposed. In our recent work, through an extensive experimental analysis, we have shown that the aforementioned assumption is not representative of current face and fingerprint presentation attacks [17]- [19]. In fact, their fake score distributions do not only rarely match those of genuine users, but they can also be very different, depending on the technique, materials, and source images used to fabricate the presentation attack; i.e., presentation attacks can have a different impact on the output of the targeted matcher.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, recent works have been developed in order to evaluate spoofing attacks in multi-modal biometric systems including [24]- [28]. In these works, the authors investigate robust fusion schemes for spoofing attacks considering face and fingerprint biometric traits.…”
Section: Other Approachesmentioning
confidence: 99%
“…A new method of personal authentication using face and palm print images in [8]. The proposed bimodal system authentication utilized a neural network for obtaining the matching score between the two biometric traits before performing fusion scores.…”
Section: A Related Researchmentioning
confidence: 99%
“…This matrix of eigenvalues is Eigen space V. The data matrix X is projected onto the Eigen space to get P consisting n columns as in equation (8). where…”
Section: Hierarchical Structural Check Matching Algorithmmentioning
confidence: 99%